Reading Interventions With Behavioral and Social Skill Outcomes: A Synthesis of Research. (January 2015) - Roberts, Garrett J.; Solis, Michael; Ciullo, Stephen; McKenna, John W.; Vaughn, Sharon
Research findings have suggested that reading deficits and problem behaviors are positively related. This synthesis investigated how reading interventions impact behavioral/social skill outcomes by reviewing studies that included (a) a reading intervention without behavioral/social skill components, (b) behavioral/social skill dependent variables, and (c) students in Grades K-12. Fifteen articles were evaluated by the type of reading intervention, associations between positive reading effects and behavioral/social skill outcomes, and The What Works Clearinghouse (WWC) determinants of study ratings. Findings suggested that reading interventions tended to have positive reading outcomes, while behavioral/social skill outcomes were small or negative. Research did not suggest an association between improved reading and behavioral performance, regardless of the WWC study determinants rating. Implications include reading instruction may not be sufficient to improve behavioral and social skill outcomes. Additional research is warranted to investigate the long-term impact of reading on behavioral and social skill outcomes.